Major postpartum hemorrhage after intra partum caesarean section: analysis of risk factors - Waheed, Arfat; Bhat, Shakura; Perniola, Andrea; Khan, Imran; Tiwary, Rimple; Tiwary, Manish Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Women who undergo intrapartum caesarean section (CS) are at increased risk of postpartum hemorrhage (PPH) compared to those undergoing elective caesarean. We aimed to find the risk factors for major post-partum hemorrhage in women undergoing intra-partum caesarean section. Methods: A retrospective chart study was conducted to identify risk factors for severe PPH in intrapartum CS. Severe PPH was classified as an estimated blood loss (EBL)≥1500 ml or receipt of a red blood cell (RBC) transfusion up to 48 hours after CS. Logistic regression was performed to identify the potential risk factors. Results: 102 cases and 189 controls were studied. Average blood loss was 1530 ml in cases and 433 ml in controls. Among severe PPH cases, 46% of women had at least 1500 ml EBL, and 83% of women received RBC intraoperatively or within 48 hours post-CS. Most significant clinical factor for severe PPH during intrapartum CS was general anesthesia (OR 4.12; CI=3.05 to 8.17). Compared to parturients who underwent primary CS, those who had ≥3 CS had increased odds of severe PPH (OR 1.83; CI=2.11-4.08). Women aged ≥30 years had reduced odds of PPH compared to women aged less than 30 years (OR=0.52; 95% CI=0.32-0.86). Arab women had 2-fold increased odds of severe PPH as compared to non-Arab women in our study (OR 2.04; CI=1.25-3.31). Conclusions: In patients undergoing intrapartum caesarean section, general anesthesia may be a risk factor for postpartum hemorrhage. The risk of severe postpartum hemorrhage may be increased in patients with, multiple previous caesareans (≥3) and multiple pregnancies. Arab ethnicity was also found to be a risk factor in this study but larger studies are needed to confirm our findings.